АКТУАЛЬНЫЕ ПРОБЛЕМЫ ПРЕПОДАВАНИЯ ТЕХНОЛОГИИ В ШКОЛЕ И ОПЫТЫ ЗАРУБЕЖНЫХ СТРАН - Камилова, М.К.; Ещанова, С.Т. (SCIENCE and SOCIETY, 2023)
Increasing the interest of schoolchildren in the subject of technology makes it possible to prepare excellent specialists who will contribute to the development of the country, socio-economic development. When not only schoolchildren, but every person understands that the subject of technology has a special place in society, the interest of schoolchildren in the subject increases. The article studied the experience of a number of developed countries, Norway, the USA, Great Britain, China in teaching the subject of technology at school.